Global governance : evaluating the liberal democratic, Chinese, and Russian solutions - Kolodziej, Edward A. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"How do we prevent the next pandemic? Will governments successfully tackle climate change? Will they find ways to close the gap between the haves and have-nots and to eliminate poverty? Which solution - democratic or authoritarian - will determine the global governance of a flawed nation-state system? This unique contribution to global studies advances a multidisciplinary theory that the governments of all human societies are the tenuous outcome of the competing solutions to the Imperatives of Order, Welfare, and Legitimacy (OWL). The OWL paradigm provides a common framework to evaluate the contrasting responses of the liberal democratic, Chinese, and Russian solutions to global governance. Underscored is the volume's contention that global governance is the overriding issue confronting nation-states and the diverse and divided peoples of what is now a global society for the first time in the evolution of the species. The volume addresses a wide spectrum of audiences, united in their shared resolve that the democracies prevail in a projected century-long struggle between democratic and authoritarian regimes to determine global governance. Scholars, teachers, students, elected officials, policy analysts, media professionals, and engaged citizens who make self-government work will profit from this visionary and provocative study"--
Toward a theory of governance : pursuit of order, welfare, and legitimacy (OWL) -- The rise of the liberal democratic solution -- The fall of the liberal democratic solution -- China and the imperative of order -- China and the imperative of welfare -- China and the imperative of legitimacy -- The Russian OWL solution for global governance -- A modest way forward.
OCLC-licensed vendor bibliographic record.
Keywords: International organization -- Philosophy; International cooperation -- Philosophy; Power (Social sciences); Human security; Legitimacy of governments; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / International Relations / Diplomacy